2020
DOI: 10.1155/2020/4297937
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Protein Self-Assembling Nanoparticle with Significant Advantages in Vaccine Development and Production

Abstract: Nanoparticles are playing an increasingly powerful role in vaccine development. Here, we report the repurposing of nonstructural proteins 10 and 11 (hereafter NSP10) from the replicase polyprotein 1a (pp1a) of the human SARS coronavirus (severe acute respiratory syndrome) as a novel self-assembling platform for bioengineered nanoparticles for a variety of applications including vaccines. NSP10 represents a 152 amino acid, 17 kD zinc finger transcription/regulatory protein which self-assembles to form a spheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The poly(I:C) adjuvant is able to activate a relatively high number of DCs in lymph nodes to generate a robust immune response. Cross-virus VLP design was also studied by Carter et al 132 SARS-CoV polyprotein 1a (pp1a) self-assembled into VLPs that were found to be effective against idiopathic pulmonary fibrosis (IPF) caused by Herpesvirus saimiri (HVS). These two studies show that VLPs developed using subunits from one virus can serve as effective vaccines against other viruses as well.…”
Section: Nanoparticles As Immunogenic Agents For Vaccinesmentioning
confidence: 99%
“…The poly(I:C) adjuvant is able to activate a relatively high number of DCs in lymph nodes to generate a robust immune response. Cross-virus VLP design was also studied by Carter et al 132 SARS-CoV polyprotein 1a (pp1a) self-assembled into VLPs that were found to be effective against idiopathic pulmonary fibrosis (IPF) caused by Herpesvirus saimiri (HVS). These two studies show that VLPs developed using subunits from one virus can serve as effective vaccines against other viruses as well.…”
Section: Nanoparticles As Immunogenic Agents For Vaccinesmentioning
confidence: 99%
“…Poly (lactic-co-glycolic acid) (PLGA) is one of the well-known member of this category which is approved by FDA for application in human body. This is due to the excellent biocompatibility and biodegradability in the human body [94]. Other examples include chitosan, and N-(2-hydroxypropyl) methacrylamide/N-isopropylacrylamide (HPMA/NIPAM) which showed promising results as intranasal vaccines against respiratory viruses Self-assembling proteins NPs: These are prepared through the oligomerization of monomeric proteins, which were found suitable for biomedical applications [95].…”
Section: Specific Examples Of Nanoparticles Against Virusesmentioning
confidence: 99%
“…A most recent example was the repurposing of nonstructural protein 10 (NSP10) from the replicase polyprotein 1a of human severe acute respiratory syndrome (SARS) coronavirus to exploit a selfassembling platform for antigen presentation and vaccine development, e.g. the truncated Herpesvirus saimiri gD protein fusion-expressed with NSP10 as a therapeutic vaccine for idiopathic pulmonary fibrosis [140]. Viruses have been proven as useful development platform for novel vaccines because of their particulate and repetitive nature.…”
Section: Subunit Vaccinesmentioning
confidence: 99%